Difficulties in teaching quantitative chemistry in the Department of Chemistry - College of Education - for pure sciences from the point of view of teachers and students (Journal of the College of Basic Education, 2022)
The methods and methods of teaching scientific subjects are among the important areas that help transform the abstract into constants in the mind and raise the level of experiences of both the teacher and the learner alike, in addition to being an integral part of the educational process and one of the important pillars on which the curricula are based because it helps students to The acquisition of skills and information and the formation of trends and inclinations that serve the objectives of teaching the subject, and since quantitative chemistry is one of the important subjects taught in the Chemistry Department - College of Education - for pure sciences, the fourth stage, so it was necessary to pay attention to it and find out the difficulties that limit the achievement of its academic goals in order to Disposing of them, in a way that reflects positively on the educational process by developing the efficiency of its teachers in a good way to serve it